New integrated concepts and measures of income poverty and of 'common prosperity' in China - Knight, J; Shi, L; Haiyuan, W (Centre for the Study of African Economies, 2023)
With incomes rising rapidly in China, measures of numbers in absolute poverty are no longer helpful for policy. A case is made for introducing a new concept and measure of relative poverty in China. Support is found from estimates of happiness functions using the 2013 national surveys of the China Household Income Project (CHIP). The Chinese government has recently introduced a new policy of promoting ‘common prosperity’. The criteria for measuring progress towards the achievement of common prosperity are analysed. A case is made for integrating the concepts of relative poverty and of common prosperity, so that households can be classified as poor, commonly prosperous, or rich. That classification is made for the 2002, 2013, and 2018 CHIP surveys.